2016
DOI: 10.1212/wnl.0000000000002808
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of risk factors for postherpetic neuralgia in herpes zoster patients

Abstract: Objective:To investigate risk factors for postherpetic neuralgia, the neuropathic pain that commonly follows herpes zoster.Methods:Using primary care data from the Clinical Practice Research Datalink, we fitted multivariable logistic regression models to investigate potential risk factors for postherpetic neuralgia (defined as pain ≥90 days after zoster, based on diagnostic or prescription codes), including demographic characteristics, comorbidities, and characteristics of the acute zoster episode. We also ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
106
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(119 citation statements)
references
References 29 publications
(38 reference statements)
7
106
2
4
Order By: Relevance
“…A recent analysis showed that postherpetic neuralgia occurred in 9.1% of patients with RA in whom HZ developed, with the incidence of postherpetic neuralgia increasing with age . In the tofacitinib development program, 7.4% of patients developed postherpetic neuralgia following their first HZ event.…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis showed that postherpetic neuralgia occurred in 9.1% of patients with RA in whom HZ developed, with the incidence of postherpetic neuralgia increasing with age . In the tofacitinib development program, 7.4% of patients developed postherpetic neuralgia following their first HZ event.…”
Section: Discussionmentioning
confidence: 99%
“…The major risk factor for PHN is old age 3) . The increased relative risk of PHN for each 10-year increment in age ranges from 1.22 to 3.11 3) .…”
Section: Discussionmentioning
confidence: 99%
“…The increased relative risk of PHN for each 10-year increment in age ranges from 1.22 to 3.11 3) . Therefore, elderly people have an increased risk of PHN after HZ infection.…”
Section: Discussionmentioning
confidence: 99%
“…Both the incidence and severity of zoster increase with age, with complications occurring in almost half of older people with zoster [29]. Post-herpetic neuralgia, a debilitating neuropathic pain syndrome, is the commonest complication, increasing notably with age – typically rates start to rise from around age 50 years – and among people with severe immunosuppression [30]. Other possible sequelae of zoster include ophthalmic involvement, a range of neurological complications including cranial nerve palsies and meningoencephalitis [21], exacerbations of underlying cardiovascular disease causing stroke and myocardial infarction [31,32] as well as the possibility of disseminated disease, predominantly among immunocompromised populations [21].…”
Section: Epidemiology Of Varicella and Herpes Zostermentioning
confidence: 99%